Effect of predation‐risk and foraging opportunities on substrate choice and strength of brightness preference in Schizothorax wangchiachii and Percocypris pingi juveniles. (8th November 2021) - Zhang, Baowen; Wu, Hui; Li, Maohua; Gan, Weixiong; Li, Tiancai; Yang, Kun; Song, Zhaobin
Abstract: Fish substrate preference may be largely influenced by genetics. However, does predator‐experience training (hatchery‐reared fish exposed to their natural predators while in captivity) or the presence of conspecifics, prey or predator affect this preference? We determined the effect of predation‐risk and foraging opportunities on substrate choice of Schizothorax wangchiachii and Percocypris pingi when in the presence of a conspecific, predator or prey. We found that both S .  wangchiachii and P .  pingi juveniles preferred the large gravel substrate, regardless of prey/predator presence or previous training. When in the presence of a predator, wild and predator‐trained hatchery‐reared S .  wangchiachii juveniles chose the white substrate over the black substrate as it was the furthest away from the predator ( Silurus meridionalis ), whereas the predator‐naïve individuals preferred the black substrate. This suggests that predation stress training could improve the ability to recognize and avoid predators in hatchery‐reared S .  wangchiachii juveniles. Wild and hatchery‐reared P .  pingi juveniles continued to choose the black substrate even though it was distant from the potential prey ( S .  wangchiachii ). The time spent by wild P .  pingi juveniles over black substrate was significantly lower than hatchery‐reared juveniles. It is possible that the wild P .  pingi juveniles' ability to recognize prey resulted in their more frequent movement towards the prey. The findings in the present study may lead to better predator/prey‐recognition training of hatchery‐reared S .  wangchiachii and P .  pingi juveniles, potentially increasing their survival rate when released to the wild.